Beginning C++20 from novice to professional - Horton, Ivor; Weert, Peter van (Apress, 2020)
Begin your programming journey with C++, starting with the basics and progressing through step-by-step examples that will help you become a proficient C++ programmer. This book includes new features from the C++20 standard like modules, concepts, ranges, and the spaceship operator. All you need are Beginning C++20 and any recent C++ compiler and you'll soon be writing real C++ programs. There is no assumption of prior programming knowledge. All language concepts that are explained in the book are illustrated with working program examples, and all chapters include exercises for you to test and practice your knowledge. Free source code downloads are provided for all examples from the text and solutions to the exercises. This latest edition has been fully updated to the latest version of the language, C++20, and to all conventions and best practices of modern C++. Beginning C++20 also introduces the elements of the C++ Standard Library that provide essential support for the C++20 language. You will: Begin programming with the C++20 standard Carry out modular programming in C++ Work with arrays and loops, pointers and references, strings, and more Write your own functions, types, and operators Discover the essentials of object-oriented programming Use overloading, inheritance, virtual functions, and polymorphism Write generic function and class templates, and make them safer using concepts Learn the ins and outs of containers, algorithms, and ranges Use auto type declarations, exceptions, move semantics, lambda expressions, and much more.
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (SpringerLink, viewed December 10, 2020)
Keywords: C++ (Computer program language); Programming languages (Electronic computers); Computer software; Computer science; Software engineering; Software; Electronic Data Processing; C++ (Langage de programmation); Logiciels; Informatique; Génie logiciel; software; Computing & information technology; Software Engineering; Programming & scripting languages: general; Computers; General; Computers; Computer Science; Computers; Software Development & Engineering; General; Computers; Programming Languages; General